Long-term rearrangement of retinal structures in a novel mutation of X-linked retinoschisis - Piermarocchi, Stefano; Miotto, Stefania; Colavito, Davide; Del Giudice, Elda; Leon, Alberta; Maritan, Veronica; Piermarocchi, Rita; Tormene, Alma Patrizia (Biomedical reports, 2017)
The aim of the present study was to report a novel mutation in the retinoschisin 1 (RS1) gene in a Caucasian family affected by X-linked juvenile retinoschisis (XLRS) and to describe the long-term modification of retinal structure. Two brothers with an early onset maculopathy were diagnosed with XLRS. Fundus photography, fluorescein angiography, spectral domain optical coherence tomography and electroretinogram analyses were performed. Their sister was also examined. All subjects were screened for mutations in the RS1 gene. XLRS patients demonstrated a marked reduction of best-corrected visual acuity. SD-OCT scans reported a cystic degeneration primarily involving the inner nuclear layer, though some cysts were detected in the outer plexiform layer and in the ganglion cell layer. During the ten-year follow-up, a progressive retinal thickening and coalescence of the cysts was observed. Genetic testing revealed a novel mutation (p.Ile212Asn) in the RS1 gene in both XLRS patients, whereas their sister was not a genetic carrier. Several mutations of the RS1 gene were recognized to be responsible for XLRS. Although the correspondence between genotype and phenotype is still under debate, is reasonable that siblings affected by XLRS could share other genetic and/or epigenetic factors capable to influence clinical course of the disease.